Avaliação da qualidade no curso de língua inglesa da Casa de Cultura Britânica de uma instituição de ensino superior - Victor, Marcos Norelle Ferreira (2021)
One of the main concerns of educational institutions, nowadays, has been to offer quality services through evaluation consultations aimed at their students and teachers. This research sought to evaluate the quality of educational services offered by a foreign language course from a Higher Education Institution. This is an applied research with a quantitative approach, in which data were collected from the perspectives of users, involving their perceptions of services aimed at the five dimensions of quality contained in the Servqual scale model: tangibility, reliability, promptness, security and empathy. The main objective of this study was to analyze the quality of services offered by the foreign language course of Casa de Cultura Britanica of a Higher Education Institution. For data analysis, Descriptive Statistics measures were used as a measure of central tendency (mean) and standard deviation. The methodology used for the research and data collection was the application of two questionnaires (both adapted from the Servqual scale) for each group of participants (students and teachers), with the purpose of evaluating the perceptions regarding the 22 variables present in the five dimensions of quality. In addition to these 22 questions, some sociodemographic questions were also applied. Through the results of this research, it was possible to verify that the degree of satisfaction of students and professors showed that, of the five dimensions of the Servqual scale, only the Tangibility dimension obtained a score lower than 4 points, as the institution does not have modern equipment. Regarding the other dimensions and attributes, the degree of satisfaction was quite positive, with emphasis on attribute 13 - The information provided by professors and administration staff of your educational institution is credible, and attribute 16 - Administrationstaff and professors of your educational institution have the knowledge necessary for the performance of their functions; by the students, and attribute 7 - The services provided by your educational institution are considered reliable by society, and attribute 10 - Administration staff demonstrate availability and interest during the service period, obtained the lowest standard deviation present in that analysis by the professors. The Readiness dimension had a higher degree of satisfaction from the professors, while the Safety dimension had the best degree of satisfaction from the students.